The Use of Mistake Buster Technique Through Quizalize in Improving Student Grammar Mastery of Eighth-Grade Students of State Islamic Junior High School - Sella Ananda Giovany; Sri Wahyuni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Although there is increasing evidence that the Mistake Buster method improves grammar learning and that gamified quiz platforms boost student motivation, these two areas of research have seldom been combined into a cohesive, theory-based intervention, especially for instructing Simple Past Tense in Indonesian madrasah environments. This research tackles the existing gap by investigating the Mistake Buster method implemented via Quizalize as a cohesive intervention, rather than considering pedagogy and technology as distinct factors, to enhance eighth-grade students' proficiency in the Simple Past Tense at State Islamic Junior High School. Anchored on Bruner (1966) discovery learning and Ellis (2015) focus-on-form methodology, the research employed an embedded mixed-methods framework (n = 32, purposive sampling) that integrated a one-group pretest-posttest design with classroom observations, surveys, and educator interviews over six sessions. The method was executed with meticulous adherence to Huynh (2003) six-step protocol, and students indicated heightened motivation, less anxiety, and enhanced collaboration. Proficiency in grammar saw a notable enhancement, reflected by an average increase of 12.81 points (p = 0.0081, Cohen's d = 0.47, indicating a medium effect), particularly among students who initially exhibited low performance; however, challenges persisted in differentiating between "was/were" and "did not + V1" structures. These results establish the integrated Mistake Buster-Quizalize method as an empirically validated, theoretically sound model for technology-enhanced grammar teaching, providing a reproducible framework for merging error-focused pedagogy with gamified formative evaluation in EFL settings.